Evaluación del rendimiento de pepinillo (Cucumis sativus L). VAR PALOMAR, en Sustratos Hidropónicos en La Esperanza Trujillo - Castillo Marcelo, Ada Edith (2017)
This research was conducted in order to evaluate the performance of Cucumis sativus L. var palomar in hydroponic substrate 50% - 50% (T1); 50% - 50% (T2); 50% - 50% (T3); 100% (T0) and identify the most appropriate substrate. The system of direct seeding in greenhouse and sleeves made; a desing of complete random (DBCA) with four treatments and three repetitions blocks used. The variables werw subjected to the test of analysis of variance and the means to test multiple ANVA significance of 5%, and determine the best treatment. It was evaluated, plant height, fruit length, fruit diameter, number of fruits per plant, yield in kg ha-1. Of the main results it was concluded that there are significant effects on crop yield of qherkin related to use four hydroponic substrates with higher yield (T0) 100% 13.24 (kg) with lower performance (T3)50% - 50% (11.35). It is recomemded to sow gherkin on the best hydroponic substrate sand quarry